(untitled) (Cardiovascular Journal, 2024)
Background: The effects of glucose abnormalities on in-hospital outcome after Primary Percutaneous Coronary Intervention (PCI) in acute STEMI remain unclear. The study assessed the relationship of admission blood glucose level to in-hospital outcome in patients presenting with a STEMI and treated with Primary PCI. Methods: This prospective study was conducted in the department of cardiology, NICVD, Dhaka Bangladesh from May 2018 to April 2019.Total 80 patients with admission normal blood glucose and hyperglycemia with acute STEMI underwent Primary PCI were considered for the study. Results: Mean age of the studied patient was 44.0±9.1 years ranging from 30 to 61 years and the mean age of the group II patients was 48.0±7.8 years ranging from 37 to 61 years. Itwas found that acute heart failure occurred 10% in group II and 2.5% in group I patients with statistically significant (p=0.04) difference. Cardiogenic shock observed 2.5% patients in group II and 2.5% patients in group I with statistically no significant (p=0.56) difference. Significant arrhythmias were found 5% patients in group II and 2.5% in group I patients with statistically no significant (p=0.40) difference. No MI and CVA were occurred in both group of patients. In group II, 2.5% patients died and no patients died in group I with statistically no significant (p=0.31) difference. Conclusion: Admission hyperglycemia is a predictor of poor prognosis in STEMI patients undergoing primary PCI. Cardiovasc j 2024; 16(2): 70-77